Revisiting the nexus between remittances and financial sector development in Nigeria - Nadabo, Yusuf Shamsuddeen (Universitas Islam Indonesia, 2023)
Purpose ― The study aims to investigate the impact of remittances on financial sector development in Nigeria using data from 1990 to 2021.Method ― The study examines the variables' relationship using the Autoregressive Distributed Lag (ARDL) and Toda Yamamoto (TY) Causality.Findings ― The study finds that remittances have a positive and significant long-run impact on financial sector development. Total reserves and imports of goods and services have a negative and significant long-run impact. In the short run, remittances and deposit interest rates positively and significantly impact financial sector development, while total reserves and total population have negative and significant impacts. The Toda-Yamamoto causality result indicates a two-way causal relationship between financial sector development and remittances.Implication ― The study recommends that the government employs policies encouraging channeling remittances through a formal banking system, as well as ensuring that such remittances received are channeled to finance productive investment, hence financial development.Originality ― The novelty of this research relates to the use of the three main indicators of remittances in an economy, which are the import of goods and services, total reserves, and deposit interest rates, to examine its impact on financial sector development in Nigeria